Metaphorical Euphemisms in Anies Baswedan’s Instagram Comments - Riska Ayunda; Putri Rizky Syafrayani; Merry Luz Molina; Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This study investigates the use of metaphorical euphemisms in Instagram comments related to Anies Baswedan, a prominent figure in Indonesian politics. The aim is to analyze how netizens use euphemisms to navigate sensitive political discourse in a digital context. Metaphorical euphemisms, defined as expressions that soften or reframe controversial or harsh topics, play a significant role in managing political expression. The research uses a qualitative content analysis approach to examine 15 Instagram comments, categorizing euphemisms into three types: analogy, distortion, and borrowing (Allan & Burridge, 2020). The findings reveal that distortion euphemisms were most common (46.67%), followed by analogy euphemisms (40%) and borrowing euphemisms (13.33%). Distortion euphemisms often reframed negative political situations in a more acceptable or humorous light, while analogy euphemisms employed vivid comparisons to communicate complex ideas in a relatable manner. Borrowing euphemisms utilized terms from other contexts to soften their meaning. The study emphasizes the importance of these linguistic strategies in fostering constructive dialogue while mitigating conflict in politically polarized environments. The findings contribute to understanding how euphemisms function in digital political communication, revealing the creativity of netizens in expressing their views. This research offers insights into the role of language in shaping public opinion and engagement in the digital age.